2018
DOI: 10.1103/physreva.97.020302
|View full text |Cite
|
Sign up to set email alerts
|

Distance scaling of electric-field noise in a surface-electrode ion trap

Abstract: We investigate anomalous ion-motional heating, a limitation to multi-qubit quantum-logic gate fidelity in trapped-ion systems, as a function of ion-electrode separation. Using a multi-zone surfaceelectrode trap in which ions can be held at five discrete distances from the metal electrodes, we measure power-law dependencies of the electric-field noise experienced by the ion on the ion-electrode distance d. We find a scaling of approximately d −4 regardless of whether the electrodes are at room temperature or cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 38 publications
11
69
1
Order By: Relevance
“…We find that the Rabi method gives heating rates that are systematically about 17% higher than for the sidebandasymmetry method. This difference is consistent with findings from other experiments [14,18] and may be linked to the non-zero projection of other motional modes on the measurement laser or laser intesnity noise. To simplify comparison of the electric-field noise across the full range of ion-surface distances, we scale the data from the Rabi-oscillation method by a constant factor of 0.85.…”
Section: A Distance Scalingsupporting
confidence: 92%
See 1 more Smart Citation
“…We find that the Rabi method gives heating rates that are systematically about 17% higher than for the sidebandasymmetry method. This difference is consistent with findings from other experiments [14,18] and may be linked to the non-zero projection of other motional modes on the measurement laser or laser intesnity noise. To simplify comparison of the electric-field noise across the full range of ion-surface distances, we scale the data from the Rabi-oscillation method by a constant factor of 0.85.…”
Section: A Distance Scalingsupporting
confidence: 92%
“…The magnitude of electric-field noise in this experiment was about an order of magnitude higher than the best published results for untreated surface traps. The second study found β = 4.0 for a multizone niobium surface trap [14]. Here, the ion trap contained several trapping zones spaced by on the order of 1 mm, where the electrodes at each zone were scaled to trap ions at different distances from the surface.…”
Section: Introductionmentioning
confidence: 99%
“…A heating rate (ṅ) of about 58 quanta s −1 has been observed for a single 9 Be + ion on a room temperature surface trap with a cleaned surface (40 μs above the trap surface, 3.6 MHz trap frequency) [126] and a silicon based trap in a cryogenic environment used to trap individual 40 Ca + ions exhibited heating rates as low as 0.33 quanta s −1 (0.6(2) quanta s −1 on average) (230 μs from the surface, 1.1 MHz trap frequency) [127]. For 171 Yb + ions located 70 μs above the trap surface with a trap frequency of 3 MHz, these heating rates correspond to expected heating rates of 0.5 quanta s −1 and 0.7 quanta s −1 assuming that the heating rate scales as ω −2.4 for fixed ion and d −4 for fixed ω [126,128]. The heavy mass of Yb + relative to Ca + and Be + results in a lower heating rate for the same spectral noise density and achieving heating rates of 1 quanta s −1 by surface cleaning or cryogenic trapping is feasible.…”
Section: Single Error Source Dominant Effectsmentioning
confidence: 78%
“…Because the measurement of electric-field noise based on trapped ions is a numerous and complicated process of operation, and the surface adatoms is not the only reason for electric-field noise. Although, the electricfield noise can be measured by trapped ions [6,9,23,24]to indirect describe the surface adatoms, it is unable to monitor in real-time and to reflect the adatoms film. In addition, our contamination measuring method for surface ion trap also can to be a new research means for anomalous heating of ions.…”
Section: Analysis and Discussionmentioning
confidence: 99%